Maintenance of service oriented architecture composite applications: static and dynamic support. Issue 1 (22nd September 2011) - White, Laura J.; Reichherzer, Thomas; Coffey, John; Wilde, Norman; Simmons, Sharon
SUMMARY Several authors have suggested that service‐oriented architecture (SOA) applications will present new program comprehension challenges for future software maintainers. We review the literature on program comprehension for SOA and describe exploratory work on static and dynamic program analysis, using two prototype tools to aid in addressing these challenges. SOAMiner is a static search tool to extract information from XML‐structured SOA files such as Web Services Description Language, XML Schema Definition Language, and Business Process Execution Language. Feature sequence viewer is a dynamic message trace analysis tool that extracts a sequence diagram highlighting the path of messages involved in processing a particular Web service request. Several case studies were conducted involving both static and dynamic analysis. Use of these tools has helped to clarify what SOA maintainers will need to know and how software tools might help them. Results revealed various types of static and dynamic information that can be useful to maintainers of SOA composite applications. Copyright © 2011 John Wiley & Sons, Ltd.